Anatomy of Brazil’s Subjective Well-Being : A Tale of Growing Discontent and Polarization in the 2010s - Burger, Martijn; Hendriks, Martijn; Ianchovichina, Elena (World Bank, Washington, DC, 2022)
After increasing for years and reaching high levels, Brazil’s subjective well-being deteriorated following the economic contraction in 2015. Using data from the Gallup World Poll for the 2010s, this paper identifies the factors that underpin Brazil’s subjective well-being and its change, paying special attention to heterogeneity across population groups. Having sufficient income, financial security, economic optimism, satisfaction with living standards and health services, social capital, tertiary education, and digital access are the main factors associated with subjective well-being. These factors matter to different extents along the income distribution and across generations and space. The decline in subjective well-being since 2015 was heterogeneous and more pronounced among men, rural residents, and the old. Economic expectations increased in importance as they assumed a greater role in people’s preferences, especially those of men, and more people grew pessimistic about the economic outlook. The decline in subjective well-being and the switch in voter support from one end of the political spectrum to the other in the 2018 general elections were both associated with the grievances triggered by the economic and leadership crisis of the mid-2010s. These grievances signal an erosion in the support for the social contract in place since the 1990s and the need to renew it.